The Effect of Work Environment, Career Ladder on Job Satisfaction and Turnover Intention as Mediating Variables at BPJS Ketenagakerjaan - Sukasrana, Gemang; Iqbal, M. Ali (International Journal of Education, Information Technology, and Others, 2024)
The purpose of this study was to determine the effect of work environment, career path on job satisfaction and turnover intention as a mediating variable in the employment bpjs. This study uses quantitative research methods, the population in this study are employees at the BPJS Employment Regional Office of Sumbarriau with a total population of 300 people. The sampling technique in this study used random sampling, and the number of samples in this study were 172 samples. The data collection method of this research is a questionnaire and literature study, and the data analysis methods used in this research are Descriptive Analysis, SEM-PLS, Outer Model, Inner Model, and Hypothesis test. The results of this study indicate that there is a negative and significant effect of work environment on turnover intention at BPJS Ketenagakerjaan. there is no effect of career path on turnover intention at BPJS Ketenagakerjaan. there is a positive and significant effect of work environment on job satisfaction, there is a positive and significant effect of career path on job satisfaction, there is no positive effect of job satisfaction on turnover intention, there is no positive effect of work environment mediated by job satisfaction on turnover intention, and there is no positive effect of career path mediated by job satisfaction on turnover intention.